Mandatory policies for influenza vaccination: Views of managers and healthcare workers in England. Issue 1 (3rd January 2019) - Stead, Martine; Critchlow, Nathan; Eadie, Douglas; Sullivan, Fay; Gravenhorst, Katja; Dobbie, Fiona
Highlights: Mandatory policies may increase uptake of flu vaccination by healthcare workers (HCWs). Our survey of managers and HCWs found little support for compulsory vaccination or face masks. Concerns related to stigma, ethics, practicality, enforceability and distress to patients. Declination forms were less strongly opposed, but the manner and context of use are important. Abstract: Introduction: Mandatory policies have the potential to increase uptake of influenza ('flu') vaccination among healthcare workers (HCWs), but concerns have been expressed about their acceptability and effectiveness. We explored views on three mandatory policies (declination forms, face masks or reduced patient contact, and mandatory vaccination) among both HCWs and flu vaccination programme managers in the National Health Service (NHS) in England. Method: A mixed method approach was employed. An online cross-sectional survey was conducted with staff responsible for implementing influenza campaigns in NHS trusts (healthcare organisations) in England ( n = 72 trusts). The survey measured perceived effectiveness of the three mandatory policies and perceived support for them among HCWs. Qualitative interviews were conducted in four trusts, with influenza campaign managers ( n = 24) and with HCWs who had the opportunity to receive the influenza vaccination ( n = 32). Interviews explored respondents' views of the three strategies and were analysed thematically using QSR NVivo 11 All data were collected shortly after the 2016/2017 influenza season. Results: In the survey, views varied on the effectiveness of the three policies and none of the interventions were thought to be strongly supported by HCWs, with particularly low levels of support perceived for mandatory vaccination and for face masks or reduced patient contact. The qualitative interviews revealed substantial concerns around the practicability and enforceability of mandatory policies and the potential discriminatory effect on HCWs who made a principled decision or had medical reasons for exemption. Additional doubts were also expressed regarding the effectiveness of face masks and their potential to worry patients, and the ethics of compelling staff to accept medical intervention. Discussion: Mandatory vaccination and face masks would not be strongly supported if introduced in the UK. If declination forms are adopted, they should be used in a constructive intelligence-gathering manner which avoids stigmatising HCWs.